Phase Inversion: A Universal Method to Create High‐Performance Porous Electrodes for Nanoparticle‐Based Energy Storage Devices. (6th October 2016) - Yang, Xiaofei; Chen, Yuqing; Wang, Meiri; Zhang, Hongzhang; Li, Xianfeng; Zhang, Huamin
Abstract : The intrinsic properties of nanoscale active materials are always excellent for energy storage devices. However, the accompanying problems of ion/electron transport limitation and active materials shedding of the whole electrodes, especially for high‐loaded electrode composed of nanoparticles with high specific surface area, bring down their comprehensive performance for practical applications. Here, this problem is solved with the as proposed "phase inversion" method, which allows fabrication of tricontinuous structured electrodes via a simple, convenient, low cost, and scalable process. During this process, the binder networks, electron paths, and ion channels can be separately interconnected, which simultaneously achieves excellent binding strength and ion/electron conductivity. This is verified by constructing electrodes with sulfur/carbon (S/C) and Li3 V2 (PO4)3 /C (LVP/C) nanoparticles, separately delivering 869 mA h g −1 at 1 C in Li–S batteries and 100 mA h g −1 at 30 C in Li–LVP batteries, increasing by 26% and 66% compared with the traditional directly drying ones. Electrodes with 7 mg cm −2 sulfur and 11 mg cm −2 LVP can also be easily coated on aluminum foil, with excellent cycling stability. Phase inversion, as a universal method to achieve high‐performance energy storage devices, might open a new area in the development of nanoparticle‐based active materials. Abstract : A scalable, energy‐saving and environmentally friendly phase inversion method is successfully used to prepare electrodes (PIEs) with tricontinuous phase structure. The as‐prepared electrodes have increased adhesive strength and improved Li + /e − transport, which leads to high active material loadings, excellent cycling stability, and good C‐rate performance for both Li–S batteries and Li‐ion batteries.